814 Evaluating the Impact of Neurosurgical Rotation Experience in Africa on the Interest and Perception of Medical Students Towards a Career in Neurosurgery: A Continental, Multi-Centre, Cross-Sectional Study. (19th August 2022) - Dada, Olaoluwa Ezekiel; Yang Ooi, Setthasorn Zhi; Bukenya, George William; Kenfack, Yves Jordan; Le, Chi; Ohonba, Efosa; Adeyemo, Emmanuel; Narain, Kapil; Awad, Ahmed Khaled; Barrie, Umaru; Sichimba, Dawin; Ogunfolaji, Oloruntoba; et al.
Abstract: Introduction: Africa has the second-highest neurosurgical workforce deficit globally, and many medical students in Africa lack exposure to the field. This study aims to assess the impact of a neurosurgical rotation during medical school in shaping the perception and interest of students towards a career in neurosurgery. Method: This is a continental, multi-centre, cross-sectional study. A Google form e-survey was disseminated to African clinical medical students between February 21st and March 20th, 2021. Data was analysed using descriptive statistics and adjusted logistic regression modelling. Results: Data was received from 539 students in 30 African countries (n=30/54, 55.6%). The majority of participants were male (n=289/539, 53.6%) and were from Kenya (n=83/539, 15.4%). Most students had undertaken a clinical neurosurgery rotation (n=278/539, 51.6%); the majority reported a rotation length of four weeks or less (n=181/278, 65.1%). Students with clinical experience were less likely to pursue the specialty (p=0.02) and had a stronger perception that it is more difficult for women to pursue neurosurgery (p=0.0001) when compared to those without clinical experience. However, after adjusting for other factors, students with greater than four weeks of neurosurgical exposure were more likely to express a career interest in neurosurgery (odds ratio [OR]=1.75, p<0.04) and men were more likely to express interest in a neurosurgical career compared to women (OR=3.22, p<0.001). Conclusions: Our findings support standardised, continent-wide, curriculum development, and advocacy supporting improved gender inclusivity in education and policymaking to improve the quality of neurosurgical exposure during medical school and help tackle the neurosurgical workforce deficit across Africa.